PLA radiation cooling fiber membrane with antibacterial performance and preparation method of PLA radiation cooling fiber membrane

The PLA/ZnO@ZIF-8 fiber membrane prepared by microwave-assisted preparation of ZnO@ZIF-8 nanoparticles combined with PLA, electrospinning and electrostatic spraying technology solved the problem of the lack of antibacterial function of existing radiation-cooled fiber fabrics, and realized the Efficient personal thermal management and health and safety guarantee, suitable for medical protective supplies.

CN119194736AInactive Publication Date: 2024-12-27SHENHUA SHENDONG COAL GRP +3

Patent Information

Application Number
CN202411592761.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing radiation-cooled fiber fabrics lack antibacterial functions, especially during the coronavirus pandemic, with challenges to personal thermal management and health safety for medical staff and outdoor workers.

Method used

Microwave-assisted preparation of ZnO@ZIF-8 nanoparticles combined with polylactic acid (PLA), and PLA/ZnO@ZIF-8 fiber membranes are prepared by electrospinning and electrostatic spraying technology to achieve high infrared emissivity, solar reflectivity and antibacterial Performance fiber membrane.

Benefits of technology

This fiber membrane not only has good radiation refrigeration effect and antibacterial properties, but also has good biocompatibility and degradability. It is suitable for medical protective products and reduces the risk of cross infection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194736A_ABST
    Figure CN119194736A_ABST
Patent Text Reader

Abstract

The invention provides a PLA radiation cooling fiber membrane with antibacterial performance and a preparation method thereof, the method comprises the following steps: S1, dissolving a zinc salt and an alkaline regulator in a solvent, uniformly stirring, and placing the mixed solution in a microwave reaction kettle to obtain ZnO nanoparticles; s2, dissolving ZnO nano-particles and 2-methylimidazole in a solvent, uniformly stirring, and putting a mixed solution into a microwave reaction kettle to obtain ZnO ZIF-8 nano-particles; s3, obtaining a polylactic acid electrostatic spinning solution; s4, a ZnO (at) ZIF-8 electrostatic spraying solution is obtained; and S5, preparing the ZnO (at) ZIF-8 modified polylactic acid fiber membrane. The prepared fiber membrane not only has a series of advantages of high infrared emissivity, high sunlight reflectivity, good outdoor refrigeration effect, excellent antibacterial performance and the like, but also has good biocompatibility and degradability, the preparation process is simple, and the fiber membrane is an individual cooling material with wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fully degradable personal protective materials, and in particular to a PLA radiation cooling fiber membrane with antibacterial properties and a preparation method thereof. Background Art

[0002] Maintaining good thermal physiological comfort is beneficial to human physical and mental health. However, certain occupational groups, such as medical staff and outdoor workers, need to bear excessive heat stress exposure and have a higher risk of heat-related diseases, and are in urgent need of personal thermal management. Although regulating the temperature of the space through ventilation and air-conditioning systems can effectively maintain human thermal comfort, this cooling method consumes a lot of power and has complex equipment, which is not suitable for outdoor workers and personal applications. Textiles based on passive radiation cooling can reflect sunlight and radiate heat into the cold outer space, providing a promising method for local cooling of the human body.

[0003] The global pandemic of coronavirus disease (COVID-19) has amplified the demand for antimicrobial protective textiles, especially for medical personnel engaged in disease surveillance and quarantine activities. In addition, the humid environment caused by excessive sweating can accelerate the reproduction of bacteria and viruses, posing a serious risk to human health. Therefore, it is crucial to design fiber textiles with bactericidal and radiant cooling functions.

[0004] Although radiative cooling fiber fabrics have been widely studied, few studies have integrated antibacterial functions into radiative fibers. Modifying fibers with nanoparticles is an efficient, simple, and inexpensive solution for daytime radiative cooling. As a representative nanoparticle, zinc oxide (ZnO) has high reflectivity to sunlight. In addition, ZnO can produce reactive oxygen species that destroy harmful microorganisms under sunlight, and is expected to give fabrics antibacterial properties after being composited with fiber fabrics. However, the inherent infrared emissivity of ZnO is low, and the wide band gap of ZnO limits the absorption of ultraviolet radiation, resulting in reduced photocatalytic activity. The design of advanced radiative cooling fiber fabrics based on ZnO still faces great challenges. Summary of the invention

[0005] Purpose of the invention: To meet the needs of outdoor workers and medical staff for high-performance personal cooling fabrics with antibacterial efficacy, the present invention uses microwave-assisted prepared ZnO@ZIF-8 nanoparticles and polylactic acid (PLA) as raw materials, and prepares PLA / ZnO@ZIF-8 fiber membranes by electrospinning combined with electrostatic spraying technology. The fiber membranes not only have a series of advantages such as high infrared emissivity, high solar reflectivity, good outdoor cooling effect, and excellent antibacterial performance, but also have good biocompatibility and degradability, and the preparation process is simple. It is an individual cooling material with broad application prospects.

[0006] The present invention provides a method for preparing a PLA radiation cooling fiber membrane with antibacterial properties, comprising the following steps:

[0007] Step S1, preparing ZnO nanoparticles: dissolving zinc salt and alkaline regulator in a solvent, stirring the obtained mixed solution evenly, placing the obtained mixed solution in a microwave reactor, centrifuging, washing and drying after the reaction is completed, to obtain ZnO nanoparticles;

[0008] Step S2, preparing ZnO@ZIF-8 nanoparticles: dissolving ZnO nanoparticles and 2-methylimidazole in a solvent, stirring the mixed solution evenly, placing the mixed solution in a microwave reactor, centrifuging, washing, and drying after the reaction is completed to obtain ZnO@ZIF-8 nanoparticles;

[0009] Step S3, preparing an electrospinning solution: dissolving polylactic acid in an organic solvent and stirring to obtain a polylactic acid electrospinning solution;

[0010] Step S4, preparing an electrostatic spray solution: dissolving ZnO@ZIF-8 nanoparticles and a dispersant in deionized water, and stirring to obtain a ZnO@ZIF-8 electrostatic spray solution;

[0011] Step S5, preparing PLA / ZnO@ZIF-8 fiber membrane: using polylactic acid electrospinning solution and ZnO@ZIF-8 electrostatic spraying solution as raw materials, preparing ZnO@ZIF-8 modified polylactic acid fiber membrane by electrospinning combined with electrostatic spraying technology, and finally placing the fiber membrane in an oven to dry for 24 hours to remove residual organic solvent.

[0012] In step S1, the zinc salt is at least one of zinc acetate, zinc nitrate, zinc sulfate and zinc chloride, and the concentration of the zinc salt is 0.005 to 1 mol / L.

[0013] In step S1, the alkaline regulator is at least one of ammonia water, sodium hydroxide, potassium hydroxide, triethanolamine, and sodium carbamate, and the pH value of the mixed solution is 8-13.

[0014] In step S1, the solvent is at least one of water, methanol, ethanol, isobutanol, n-butanol, isopropanol, and dimethylformamide.

[0015] In step S1, the output power of the microwave reactor is 500-6000W, the reaction temperature is 90-500°C, the reaction time is 1-60 minutes, and the diameter of the obtained ZnO nanoparticles is 10nm-400nm, and the aspect ratio is 1-3.

[0016] In step S2, the concentration of the ZnO nanoparticles is 0.001 to 0.5 mol / L, and the molar ratio of the ZnO nanoparticles to 2-methylimidazole is 1:25 to 1:5;

[0017] The solvent is at least one of water, methanol, ethanol, isobutanol, n-butanol, isopropanol, and dimethylformamide;

[0018] The microwave reactor has an output power of 300-2000W, a reaction temperature of 30-200°C, a reaction time of 5-90 minutes, and the diameter of the obtained ZnO@ZIF-8 nanoparticles is 15nm-500nm, and the aspect ratio is 1-3.

[0019] In step S3, the organic solvent is at least one of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane, and chloroform, and the concentration of the polylactic acid in the solution is 1 to 40 wt%.

[0020] In step S4, the concentration of the ZnO@ZIF-8 nanoparticles in deionized water is 0.01 to 20 wt %;

[0021] The dispersant is at least one of hexadecyltrimethylammonium bromide, polyvinyl pyrrolidone, polyvinyl alcohol, sodium hexadecylbenzenesulfonate, and sodium dodecyl sulfate, and the mass ratio of the dispersant to ZnO@ZIF-8 is 1:1000 to 1:10.

[0022] In step S5, the voltage in the electrospinning and electrostatic spraying process is 10-30 kV, the electrospinning solution consumption rate is 0.5-10 mL / h, the electrostatic spray solution consumption rate is 0.5-10 mL / h, the drum speed is 100 rpm-5000 rpm, the receiving distance is 10-25 cm, the temperature is 0-40 ° C, the relative humidity is 20-90%, and the average diameter of the obtained polylactic acid fiber is 200-3000 nm, and the fiber membrane thickness is 200-500 μm.

[0023] The present invention also provides a PLA radiation cooling fiber membrane with antibacterial properties, which is prepared by the method described above and can be used in medical protection products, such as antibacterial masks and protective clothing. The high infrared emissivity and sunlight reflection ability of the membrane enable it to have a good cooling effect in a hot environment, improving the thermal comfort of the wearer. The antibacterial property helps to inhibit the growth of bacteria and reduce the risk of cross infection. Its good biocompatibility and degradability provide an environmentally friendly and efficient solution for medical protection.

[0024] Beneficial effects: The present invention provides a PLA radiation cooling fiber membrane with antibacterial properties and a preparation method thereof. Microwave-assisted preparation of ZnO@ZIF-8 nanoparticles is adopted. ZnO@ZIF-8 nanoparticles and PLA are used as raw materials. The PLA / ZnO@ZIF-8 fiber membrane with excellent radiation cooling effect and high-efficiency photocatalytic antibacterial performance is obtained by electrospinning combined with electrostatic spraying technology. The average infrared emissivity of the fiber membrane is 93.1% to 97.5%, the average solar reflectivity is 93.4% to 98.1%, the average outdoor cooling temperature is 9.5 to 13.6°C, the antibacterial rate against Escherichia coli is 95.6% to 99.9%, and the antibacterial rate against Staphylococcus aureus is 95.6% to 99.9%. It not only has a series of advantages such as high infrared emissivity, high solar reflectivity, good outdoor cooling effect, excellent antibacterial performance, etc., but also has good biocompatibility and degradability, and the preparation process is simple. It is an individual cooling material with broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0026] Figure 1 It is a flow chart of the method of the present invention.

[0027] Figure 2 is a scanning electron microscope image of the ZnO nanoparticles in Example 1.

[0028] Figure 3 is a scanning electron microscope image of ZnO@ZIF-8 nanoparticles in Example 1.

[0029] Figure 4 This is a scanning electron microscope image of the polylactic acid fiber membrane modified with ZnO@ZIF-8 in Example 1. DETAILED DESCRIPTION

[0030] Example 1

[0031] like Figure 1 As shown, this embodiment provides a method for preparing a PLA radiation cooling fiber membrane with antibacterial properties, comprising the following steps:

[0032] S6. Preparation of ZnO nanoparticles: Dissolve zinc acetate in deionized water (the concentration of zinc acetate is 0.2 mol / L), add sodium hydroxide until the pH value of the solution is 8, stir well and place the mixed solution into a microwave reactor (the output power of the microwave reactor is 800 W, the reaction temperature is 120° C., and the reaction time is 10 minutes). After the reaction, centrifuge, wash and dry to obtain ZnO nanoparticles with an average diameter of 150 nm and an aspect ratio of 1.2;

[0033] S7. Preparation of ZnO@ZIF-8 nanoparticles: Dissolve ZnO nanoparticles (ZnO concentration is 0.016 mol / L) and 2-methylimidazole (the molar ratio of ZnO nanoparticles to 2-methylimidazole is 1:10) in water / dimethylformamide (volume ratio is 3:1), stir evenly, and place the mixed solution in a microwave reactor (microwave reactor output power is 800 W, reaction temperature is 120°C, reaction time is 20 minutes), centrifuge, wash, and dry after the reaction to obtain ZnO@ZIF-8 nanoparticles with an average diameter of 200 nm and an aspect ratio of 1.4;

[0034] S8. Preparing an electrospinning solution: dissolving polylactic acid in dichloromethane / dimethylformamide (mass ratio 7:3) (polylactic acid concentration in the solution is 10 wt%), and stirring to obtain an electrospinning solution;

[0035] S9. Prepare an electrostatic spray solution: dissolve ZnO@ZIF-8 nanoparticles (concentration of 4 wt%) and polyvinyl alcohol (the mass ratio of polyvinyl alcohol to ZnO@ZIF-8 is 1:100) in deionized water, and stir to obtain a ZnO@ZIF-8 electrostatic spray solution;

[0036] S10. Preparation of PLA / ZnO@ZIF-8 fiber membrane: Using polylactic acid electrospinning solution and ZnO@ZIF-8 electrostatic spray solution as raw materials, ZnO@ZIF-8 modified polylactic acid fiber membrane was prepared by electrospinning combined with electrostatic spraying technology. The voltage was 20 kV, the electrospinning solution consumption rate was 1 mL / h, the electrostatic spray solution consumption rate was 2 mL / h, the drum speed was 500 rpm, the receiving distance was 15 cm, the temperature was 25 °C, and the relative humidity was 30%. Finally, the fiber membrane was placed in an oven for 24 hours to remove residual organic solvent to obtain the target ZnO@ZIF-8 modified polylactic acid fiber membrane with an average fiber diameter of 500 nm and a fiber membrane thickness of 300 μm.

[0037] Example 2

[0038] This embodiment provides a method for preparing a PLA radiation cooling fiber membrane with antibacterial properties, comprising the following steps:

[0039] S11. Preparation of ZnO nanoparticles: Dissolve zinc nitrate in ethanol (the concentration of zinc nitrate is 0.8 mol / L), add sodium hydroxide until the pH value of the solution is 13, stir evenly and place the mixed solution into a microwave reactor (the output power of the microwave reactor is 500 W, the reaction temperature is 90° C., and the reaction time is 20 minutes). After the reaction is completed, centrifuge, wash, and dry to obtain ZnO nanoparticles with an average diameter of 150 nm and an aspect ratio of 1.2;

[0040] S12. Preparation of ZnO@ZIF-8 nanoparticles: ZnO nanoparticles (ZnO concentration is 0.016 mol / L) and 2-methylimidazole (the molar ratio of ZnO nanoparticles to 2-methylimidazole is 1:10) are dissolved in ethanol, and after stirring evenly, the mixed solution is placed in a microwave reactor (the output power of the microwave reactor is 800 W, the reaction temperature is 120°C, and the reaction time is 55 minutes). After the reaction is completed, centrifugation, washing, and drying are performed to obtain ZnO@ZIF-8 nanoparticles with an average diameter of 400 nm and an aspect ratio of 2.5;

[0041] S13. Preparation of electrospinning solution: dissolving polylactic acid in acetone (polylactic acid concentration in the solution is 30 wt%), and stirring to obtain an electrospinning solution;

[0042] S14. Preparing an electrostatic spray solution: dissolving ZnO@ZIF-8 nanoparticles (concentration of 1 wt%) and hexadecyltrimethylammonium bromide (the mass ratio of hexadecyltrimethylammonium bromide to ZnO@ZIF-8 is 1:500) in deionized water, and stirring to obtain a ZnO@ZIF-8 electrostatic spray solution;

[0043] S15. Preparation of PLA / ZnO@ZIF-8 fiber membrane: Using polylactic acid electrospinning solution and ZnO@ZIF-8 electrostatic spray solution as raw materials, ZnO@ZIF-8 modified polylactic acid fiber membrane was prepared by electrospinning combined with electrostatic spraying technology. The voltage was 15 kV, the electrospinning solution consumption rate was 8 mL / h, the electrostatic spray solution consumption rate was 1 mL / h, the drum speed was 1000 rpm, the receiving distance was 20 cm, the temperature was 25 °C, and the relative humidity was 30%. Finally, the fiber membrane was placed in an oven for 24 hours to remove residual organic solvent to obtain the target ZnO@ZIF-8 modified polylactic acid fiber membrane with an average fiber diameter of 2.6 μm and a fiber membrane thickness of 350 μm.

[0044] Example 3

[0045] This embodiment provides a method for preparing a PLA radiation cooling fiber membrane with antibacterial properties, comprising the following steps:

[0046] S16. Preparation of ZnO nanoparticles: Dissolve zinc chloride in deionized isopropanol (the concentration of zinc chloride is 0.01 mol / L), add sodium hydroxide until the pH value of the solution is 11, stir well and place the mixed solution into a microwave reactor (the output power of the microwave reactor is 3000 W, the reaction temperature is 240°C, and the reaction time is 5 minutes). After the reaction, centrifuge, wash and dry to obtain ZnO nanoparticles with an average diameter of 20 nm and an aspect ratio of 2.5;

[0047] S17. Preparation of ZnO@ZIF-8 nanoparticles: Dissolve ZnO nanoparticles (ZnO concentration is 0.4 mol / L) and 2-methylimidazole (the molar ratio of ZnO nanoparticles to 2-methylimidazole is 1:20) in dimethylformamide, stir evenly, and place the mixed solution in a microwave reactor (the output power of the microwave reactor is 800 W, the reaction temperature is 80° C., and the reaction time is 10 minutes). After the reaction is completed, centrifuge, wash, and dry to obtain ZnO@ZIF-8 nanoparticles with an average diameter of 35 nm and an aspect ratio of 2.5;

[0048] S18. Preparing an electrospinning solution: dissolving polylactic acid in dichloromethane (the concentration of polylactic acid in the solution is 30 wt %), and stirring to obtain an electrospinning solution;

[0049] S19. Preparing an electrostatic spray solution: dissolving ZnO@ZIF-8 nanoparticles (concentration of 15 wt%) and polyvinyl alcohol (the mass ratio of polyvinyl alcohol to ZnO@ZIF-8 is 1:10) in deionized water, and stirring to obtain a ZnO@ZIF-8 electrostatic spray solution;

[0050] S20. Preparation of PLA / ZnO@ZIF-8 fiber membrane: Using polylactic acid electrospinning solution and ZnO@ZIF-8 electrostatic spray solution as raw materials, ZnO@ZIF-8 modified polylactic acid fiber membrane was prepared by electrospinning combined with electrostatic spraying technology. The voltage was 20 kV, the electrospinning solution consumption rate was 2 mL / h, the electrostatic spray solution consumption rate was 2 mL / h, the drum speed was 500 rpm, the receiving distance was 20 cm, the temperature was 25 °C, and the relative humidity was 30%. Finally, the fiber membrane was placed in an oven for 24 hours to remove residual organic solvents to obtain the target ZnO@ZIF-8 modified polylactic acid fiber membrane with an average fiber diameter of 700 nm and a fiber membrane thickness of 350 μm.

[0051] Example 4

[0052] This embodiment provides a method for preparing a PLA radiation cooling fiber membrane with antibacterial properties, comprising the following steps:

[0053] S21. Preparation of ZnO nanoparticles: Dissolve zinc chloride in deionized isopropanol (the concentration of zinc chloride is 0.3 mol / L), add sodium hydroxide until the pH value of the solution is 13, stir well and place the mixed solution in a microwave reactor (the output power of the microwave reactor is 100 W, the reaction temperature is 100 ° C, and the reaction time is 10 minutes). After the reaction, centrifuge, wash and dry to obtain ZnO nanoparticles having an average diameter of 200 nm and an aspect ratio of 1.4;

[0054] S22. Preparation of ZnO@ZIF-8 nanoparticles: ZnO nanoparticles (ZnO concentration is 0.002 mol / L) and 2-methylimidazole (the molar ratio of ZnO nanoparticles to 2-methylimidazole is 1:10) are dissolved in n-butanol, and the mixed solution is placed in a microwave reactor (the output power of the microwave reactor is 800 W, the reaction temperature is 120°C, and the reaction time is 20 minutes) after stirring. After the reaction is completed, centrifugation, washing, and drying are performed to obtain ZnO@ZIF-8 nanoparticles with an average diameter of 260 nm and an aspect ratio of 1.3;

[0055] S23. Preparation of electrospinning solution: dissolving polylactic acid in dichloromethane / dimethylformamide (mass ratio 8:2) (polylactic acid concentration in the solution is 5 wt %), and stirring to obtain an electrospinning solution;

[0056] S24. Preparing an electrostatic spray solution: dissolving ZnO@ZIF-8 nanoparticles (concentration of 1 wt%) and polyvinyl alcohol (the mass ratio of polyvinyl alcohol to ZnO@ZIF-8 is 1:10) in deionized water, and stirring to obtain a ZnO@ZIF-8 electrostatic spray solution;

[0057] S25. Preparation of PLA / ZnO@ZIF-8 fiber membrane: Using polylactic acid electrospinning solution and ZnO@ZIF-8 electrostatic spray solution as raw materials, ZnO@ZIF-8 modified polylactic acid fiber membrane was prepared by electrospinning combined with electrostatic spraying technology. The voltage was 30 kV, the electrospinning solution consumption rate was 0.5 mL / h, the electrostatic spray solution consumption rate was 0.5 mL / h, the drum speed was 2000 rpm, the receiving distance was 15 cm, the temperature was 25 °C, and the relative humidity was 30%. Finally, the fiber membrane was placed in an oven for 24 hours to remove residual organic solvents to obtain the target ZnO@ZIF-8 modified polylactic acid fiber membrane with an average fiber diameter of 250 nm and a fiber membrane thickness of 400 μm.

[0058] Comparative Example 1 (polylactic acid fiber membrane without ZnO@ZIF-8 modification)

[0059] The polylactic acid fiber membrane was basically prepared by the method of Example 1. The difference is that ZnO@ZIF-8 is not loaded onto the polylactic acid fiber in this example. Specifically, polylactic acid was dissolved in dichloromethane / dimethylformamide (mass ratio 7:3) (polylactic acid concentration in the solution was 10wt%), and stirred evenly to obtain an electrospinning solution; the polylactic acid electrospinning solution was used as a raw material, and the polylactic acid fiber membrane was prepared by electrospinning technology, the voltage was 20kV, the electrospinning solution consumption rate was 1mL / h, the drum speed was 500rpm, the receiving distance was 15cm, the temperature was 25°C, the relative humidity was 30%, and finally the fiber membrane was placed in an oven for 24h to remove the residual organic solvent, and the target polylactic acid fiber membrane without ZnO@ZIF-8 modification was obtained, the average fiber diameter was 500nm, and the fiber membrane thickness was 300μm.

[0060] Comparative Example 2 (PLA / ZnO fiber membrane)

[0061] The method of Example 4 was basically adopted to prepare the polylactic acid fiber membrane. The difference is that ZnO was used to modify the polylactic acid fiber in this example. Specifically, zinc chloride was dissolved in deionized isopropanol (the concentration of zinc chloride was 0.3 mol / L), sodium hydroxide was added until the pH value of the solution was 13, and the mixed solution was placed in a microwave reactor after stirring (the output power of the microwave reactor was 100 W, the reaction temperature was 100°C, and the reaction time was 10 minutes). After the reaction was completed, it was centrifuged, washed, and dried to obtain ZnO nanoparticles with an average diameter of 200 nm and an aspect ratio of 1.4; polylactic acid was dissolved in dichloromethane / dimethylformamide (mass ratio 8:2) (the concentration of polylactic acid in the solution was 5wt%), and stirred evenly to obtain an electrospinning solution; ZnO nanoparticles (concentration of 1wt%) and polyvinyl alcohol (polyvinyl alcohol and ZnO The mass ratio of ZnO to ZnO is 1:10) and dissolved in deionized water, and the mixture is stirred evenly to obtain a ZnO electrostatic spray solution; using the polylactic acid electrospinning solution and the ZnO electrostatic spray solution as raw materials, the ZnO-modified polylactic acid fiber membrane is prepared by electrospinning combined with electrostatic spraying technology, the voltage is 30 kV, the electrospinning solution consumption rate is 0.5 mL / h, the electrostatic spray solution consumption rate is 0.5 mL / h, the drum speed is 2000 rpm, the receiving distance is 15 cm, the temperature is 25°C, and the relative humidity is 30%. Finally, the fiber membrane is placed in an oven and dried for 24 hours to remove the residual organic solvent to obtain the target ZnO-modified polylactic acid fiber membrane with an average fiber diameter of 250 nm and a fiber membrane thickness of 400 μm.

[0062] Structural characterization and performance testing:

[0063] Scanning electron microscope observation: The microstructure of Janus polylactic acid cooling fiber membrane was observed by field emission scanning electron microscope (model SU8220, HITACHI) ( Figure 2 , Figure 3 ).

[0064] Solar reflectivity test: The reflectivity of the fiber membrane at 300-2500 nm was measured using an ultraviolet-visible-near infrared spectrophotometer (model UV-3600, Shimadzu).

[0065] Infrared reflectivity test: The infrared reflectivity and transmittance of the fiber membrane at 8-13 μm were measured using an FTIR spectrometer (model NEXUS-670, Thermo Fisher) equipped with a diffuse gold integrating sphere (PIKE Technologies).

[0066] Outdoor cooling performance test: The cooling performance of the fiber membrane was measured outdoors (11:00-13:00, August 25, 2024, Xuzhou). The simulated skin (insulating foam wrapped in aluminum foil) was heated using a silicone rubber heating plate and the temperature was maintained at 37°C. A K-type thermocouple (model YET-640X, Dickway) was used to record the temperature difference between the fiber membrane under the membrane and the exposed simulated skin.

[0067] Photocatalytic antibacterial performance test: The plate count method was used to determine the antibacterial performance of the nanofiber membrane. Referring to the standard GB / T31402-2015, Escherichia coli and Staphylococcus aureus were selected as test bacteria to conduct antibacterial tests on the fiber membrane. The fiber membrane was placed in a well plate, and the bacterial solution was dripped into the well plate. It was irradiated for 3 minutes under a solar simulator (model HSX-F300 NbeT). The bacterial solution in the well plate was dripped into a culture dish and cultured at 37.5°C and a relative humidity of 75% RH. After 12 hours, the number of colonies on the culture medium was counted.

[0068] Experimental results: Figure 2 and Figure 3 As shown, the ZnO nanoparticles and ZnO@ZIF-8 nanoparticles synthesized with microwave assistance in Example 1 have regular structures, and their average diameters are 150 nm and 200 nm, respectively. The change in particle diameter further proves the effective coating of ZnO by ZIF-8. Figure 4 The PLA / ZnO@ZIF-8 fiber membrane was prepared by electrospinning combined with electrostatic spraying technology. ZnO@ZIF-8 was evenly anchored on the surface of PLA fibers by electrostatic spraying.

[0069] Table 1 compares the test results of the average infrared emissivity, average solar reflectivity, radiation cooling temperature, and photocatalytic antibacterial properties of the polylactic acid fiber membranes obtained in the examples and comparative examples. Examples 1-4 have a higher average infrared emissivity (94.4%-96.4%), because the rich chemical bond vibrations in ZnO@ZIF-8 greatly enhance the emission of infrared light by the fiber membrane. Compared with Examples 1-4, the vibrations of the fiber membranes of Comparative Examples 1 and 2 that effectively overlap with the atmospheric window are reduced, showing lower average infrared emissivities of 71.6% and 85.1%, respectively.

[0070] Table 1

[0071]

[0072] Examples 1 to 4 all have high solar reflectivity (94.2%-97.0%), which is due to the randomly stacked fiber structure of the fiber membrane and the enhanced light scattering of ZnO@ZIF-8 nanoparticles. The average solar reflectivity of Comparative Example 2 is 85.1%, which is lower than that of Examples 1-4, proving that the composite of ZIF-8 enhances the light scattering rate of ZnO, which may be due to the polyhedral structure of ZnO@ZIF-8 nanoparticles effectively expanding the scattering cross section, which contributes to the strong scattering of incident light. The polylactic acid fiber membrane without ZnO@ZIF-8 modification in Comparative Example 1 exhibits the lowest solar reflectivity, which is 79.3%.

[0073] Examples 1 to 4 exhibited good radiative cooling performance (cooling temperature: 10.8-11.9°C), which was due to their high infrared emission and high solar light emissivity. Comparative Examples 1 and 2 had poor radiative cooling performance, with cooling temperatures of 2.4°C and 6.3°C, respectively.

[0074] In comparative example 1, the antibacterial rates of the fiber membrane against Escherichia coli and Staphylococcus aureus were as low as 20.5% and 18.6%, indicating that the pure PLA fiber membrane does not have effective antibacterial properties. In comparative example 2, the antibacterial rates of the fiber membrane against Escherichia coli and Staphylococcus aureus were 78.9% and 81.5%, respectively, indicating that the introduction of ZnO nanoparticles can give PLA fibers photocatalytic antibacterial properties. Examples 1-4 all showed excellent photocatalytic antibacterial properties (the antibacterial rate of Escherichia coli was 97.6%-99.9%, and the antibacterial rate of Staphylococcus aureus was 99.9%), indicating that PLA / ZnO@ZIF-8 fiber membrane can be used for comprehensive air disinfection under sunlight. The reason why the antibacterial performance of Examples 1-4 is better than that of Comparative Example 2 may be that ZnO@ZIF-8 forms a core-shell heterogeneous structure, the band gap energy increases, and the introduction of ZIF-8 greatly improves the ability of ZnO nanoparticles to produce active free radicals under light excitation.

[0075] It can be seen that the technical solution proposed in the present invention enables the PLA / ZnO@ZIF-8 fiber membrane to have excellent radiation cooling effect and excellent photocatalytic antibacterial ability, which is likely due to: (1) the silica nanoparticles obtained by the microwave-assisted method are uniform in size and regular in structure, and are well distributed on the fiber surface; (2) the randomly stacked fiber structure and the enhanced light scattering of ZnO@ZIF-8 nanoparticles make the PLA / ZnO@ZIF-8 fiber membrane have high solar emissivity; (3) the rich chemical bond vibrations within the atmospheric transparent window of ZnO@ZIF-8 nanoparticles make the PLA / ZnO@ZIF-8 fiber membrane have high infrared emissivity; (4) under the irradiation of sunlight, ZnO@ZIF-8 can produce active free radicals, which makes the PLA / ZnO@ZIF-8 fiber membrane have antibacterial properties.

[0076] The present invention provides a PLA radiation cooling fiber film with antibacterial properties and a preparation method thereof. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A method for preparing a PLA radiation cooling fiber membrane with antibacterial properties, characterized in that: The following steps are involved: Step S1, preparing ZnO nanoparticles: dissolving zinc salt and alkaline regulator in a solvent, stirring the obtained mixed solution evenly, placing the obtained mixed solution in a microwave reactor, centrifuging, washing and drying after the reaction is completed, to obtain ZnO nanoparticles; Step S2, preparing ZnO@ZIF-8 nanoparticles: dissolving ZnO nanoparticles and 2-methylimidazole in a solvent, stirring the mixed solution evenly, placing the mixed solution in a microwave reactor, centrifuging, washing, and drying after the reaction is completed to obtain ZnO@ZIF-8 nanoparticles; Step S3, preparing an electrospinning solution: dissolving polylactic acid in an organic solvent and stirring to obtain a polylactic acid electrospinning solution; Step S4, preparing an electrostatic spray solution: dissolving ZnO@ZIF-8 nanoparticles and a dispersant in deionized water, and stirring to obtain a ZnO@ZIF-8 electrostatic spray solution; Step S5, preparing PLA / ZnO@ZIF-8 fiber membrane: using polylactic acid electrospinning solution and ZnO@ZIF-8 electrostatic spraying solution as raw materials, preparing ZnO@ZIF-8 modified polylactic acid fiber membrane by electrospinning combined with electrostatic spraying technology, and finally placing the fiber membrane in an oven to dry for 24 hours to remove residual organic solvent.

2. The method according to claim 1, characterized in that: In step S1, the zinc salt is at least one of zinc acetate, zinc nitrate, zinc sulfate and zinc chloride, and the concentration of the zinc salt is 0.005 to 1 mol / L.

3. The method according to claim 2, characterized in that In step S1, the alkaline regulator is at least one of ammonia water, sodium hydroxide, potassium hydroxide, triethanolamine, and sodium carbamate, and the pH value of the mixed solution is 8-13.

4. The method according to claim 3, characterized in that In step S1, the solvent is at least one of water, methanol, ethanol, isobutanol, n-butanol, isopropanol, and dimethylformamide.

5. The method according to claim 4, characterized in that In step S1, the output power of the microwave reactor is 500-6000W, the reaction temperature is 90-500°C, the reaction time is 1-60 minutes, and the diameter of the obtained ZnO nanoparticles is 10nm-400nm, and the aspect ratio is 1-3.

6. The method according to claim 5, characterized in that In step S2, the concentration of the ZnO nanoparticles is 0.001 to 0.5 mol / L, and the molar ratio of the ZnO nanoparticles to 2-methylimidazole is 1:25 to 1:5; The solvent is at least one of water, methanol, ethanol, isobutanol, n-butanol, isopropanol, and dimethylformamide; The microwave reactor has an output power of 300-2000W, a reaction temperature of 30-200°C, a reaction time of 5-90 minutes, and the diameter of the obtained ZnO@ZIF-8 nanoparticles is 15nm-500nm, and the aspect ratio is 1-3.

7. The method according to claim 6, characterized in that In step S3, the organic solvent is at least one of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane, and chloroform, and the concentration of the polylactic acid in the solution is 1 to 40 wt%.

8. The method according to claim 7, characterized in that In step S4, the concentration of the ZnO@ZIF-8 nanoparticles in deionized water is 0.01 to 20 wt %; The dispersant is at least one of hexadecyltrimethylammonium bromide, polyvinyl pyrrolidone, polyvinyl alcohol, sodium hexadecylbenzenesulfonate, and sodium dodecyl sulfate, and the mass ratio of the dispersant to ZnO@ZIF-8 is 1:1000 to 1:

10.

9. The method according to claim 8, characterized in that In step S5, the voltage in the electrospinning and electrostatic spraying process is 10-30 kV, the electrospinning solution consumption rate is 0.5-10 mL / h, the electrostatic spray solution consumption rate is 0.5-10 mL / h, the drum speed is 100 rpm-5000 rpm, the receiving distance is 10-25 cm, the temperature is 0-40 ° C, the relative humidity is 20-90%, and the average diameter of the obtained polylactic acid fiber is 200-3000 nm, and the fiber membrane thickness is 200-500 μm.

10. A PLA radiation cooling fiber membrane with antibacterial properties, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing silver-doped ZnO@ZIF-8 nanoflower compound

    CN109954481A

  • Preparation method of metal particle@ ZIFs core-shell particles

    CN111100302A

  • Nanofiber filtering membrane and preparation method and application thereof

    CN117225204A

  • ZIF-8 polylactic acid composite filter membrane and preparation method thereof

    CN117225207A

  • Preparation method of hollow flower-shaped ZnO and ZIF-8 heterogeneous gas-sensitive material

    CN118624680A

Cited By

  • Radiation cooling coating with temperature self-adaptive thermal regulation function as well as preparation method and application of radiation cooling coating

    CN121379290A

  • A temperature-adaptive thermoregulated radiative cooling coating, method of preparation and use thereof

    CN121379290B